Development of an algorithm to classify children’s works: approaches from computational thinking - Camillo, Everton da Silva [UNESP] (Universidad Nacional de La Plata, 2023)
The purpose of this study is to approximate the classification process in libraries with computational thinking, a theoretical aspect present in computer science and, more recently, in other fields of knowledge such as information science. The study’s goal is to present an algorithm for precisely and computationally classifying works of children’s literature. The Content Analysis research method was used to analyze the color classification table in the document Guide for the standardization of Vila Velha school libraries network. Three analytical categories were developed a posteriori using the critical thinking skill. The study’s findings revealed three inaccuracies in the color classification table, namely: mutual coverage in classification; incompatibility in the genus-species relationship; incompatibility with the nature of information thematic representation. An algorithm was presented that allows for the precise and computational classification of works of children’s literature. The study concludes that computational thinking can be a process that organizes library classification activity, ensuring accuracy in information thematic representation due to the logical-computational character amalgamated throughout the process flow.
Desarrollo de un algoritmo para clasificar obras infantiles: aproximaciones desde el pensamiento computacional
Desenvolvimento de um algoritmo para classificar obras infantis: abordagens Desenvolvimento de um algoritmo para classificar obras infantis: partir do pensamento computacional abordagens a partir do pensamento computacional
Keywords: Algorithms; Automation; Bibliographic classification; Children’s literature; School library